2018
DOI: 10.1038/s41598-018-22746-3
|View full text |Cite|
|
Sign up to set email alerts
|

Fully Printed Wearable Vital Sensor for Human Pulse Rate Monitoring using Ferroelectric Polymer

Abstract: The ability to monitor subtle changes in vital and arterial signals using flexible devices attached to the human skin can be valuable for the detection of various health conditions such as cardiovascular disease. Conventional Si device technologies are being utilised in traditional clinical systems; however, its fabrication is not easy owing to the difficulties in adapting to conventional processes. Here, we present the development of a fully printed, wearable, ferroelectric-polymer vital sensor for monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 54 publications
2
66
0
Order By: Relevance
“…Wearable and flexible electronics, such as ion‐sensor arrays, biosensor chips, and vital sensor patches,41–46 have attracted huge attentions due to their potential applications in healthcare. One important function of vital sensor is to monitor the heart rate and there are several different implementations for such function.…”
Section: Heart Rate Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearable and flexible electronics, such as ion‐sensor arrays, biosensor chips, and vital sensor patches,41–46 have attracted huge attentions due to their potential applications in healthcare. One important function of vital sensor is to monitor the heart rate and there are several different implementations for such function.…”
Section: Heart Rate Detectionmentioning
confidence: 99%
“…One important function of vital sensor is to monitor the heart rate and there are several different implementations for such function. Organic photodetectors41,47 for heart rate sensing have been studied and reported. Working with LED, a photodetector can detect the light absorptance or scattering variation usually on fingertip or earlobe caused by the peripheral arterial blood flow.…”
Section: Heart Rate Detectionmentioning
confidence: 99%
“…For the second semicycles 2 and 4, only the second and the third terms are present as the molecular dipoles are already oriented in the previous semicycles. [21] Figure 5c shows P r as a function of the amplitude of the applied electric field. Hysteresis loops are determined by integrating the first term, i.e., the current solely from the orientation of dipoles, which is attained by subtracting the current in the second semicycle from that in the first semicycle.…”
Section: Also Shown Inmentioning
confidence: 99%
“…[18][19][20][21] Hübler et al reported, for the first time, piezoelectric P(VDF-TrFE) loudspeakers mass printed on conventional paper substrates. Printing is a convenient method for low-cost mass production.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of a fully integrated sensor device that conforms flexibly to the human body is still a challenging task . Recently, the printing technology has emerged as a low‐cost, environment‐friendly mass manufacturing technology for the fabrication of next‐generation printed flexible devices based on thin‐film transistors . Organic semiconducting materials are particularly suitable for printed electronics, because they are flexible and solution‐processable.…”
Section: Introductionmentioning
confidence: 99%